The moderating role of AI governance and ethics in the impact of AI adoption in auditing on the confidence of financial statement users - BEN AHMED, Mohamed Elhadi; BOUALLALA, Aicha (The International tax journal, 2025)
This study investigates the impact of Artificial Intelligence (AI) adoption in auditing on the confidence of financial statement users, while examining the moderating role of AI governance and ethics. Using a quantitative, cross-sectional research design and data collected through a structured questionnaire from financial statement users, the study applies Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the proposed relationships. The findings reveal that AI adoption in auditing has a strong, statistically significant positive effect on user confidence, demonstrating the value stakeholders attribute to AI-enhanced audit procedures for improving accuracy, reliability, and efficiency. Although AI governance and ethics do not have a significant direct effect on user confidence, they play a meaningful moderating role, reducing the strength of the relationship between AI adoption and confidence. This suggests that governance frameworks encourage more cautious and informed trust in AI-generated audit results. Overall, the study contributes to the growing literature on technology-driven auditing by integrating AI adoption, user confidence, and governance considerations into a unified empirical model, offering practical insights for audit firms, regulators, and policymakers.